Ureasil-polyether hybrid blend with tuneable hydrophilic/hydrophobic features based on U-PEO1900 and U-PPO400 mixtures - Molina, Eduardo F. [UNESP]; Nogueira Jesus, Celso R. [UNESP]; Chiavacci, Leila A. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Briois, Valerie; Santilli, Celso Valentim [UNESP] (Springer, 2014)
Urea-cross-linked polyether-siloxane hybrid blends with tuneable hydrophilic/hydrophobic features were prepared from a mixture of poly(ethylene oxide) (PEO1900) and poly(propylene oxide) (PPO400), hybridized by end-chain functionalization with (3-isocyanatopropyl)triethoxysilane. The aim of this study was to demonstrate that the combination of the different polyether phases produces materials with hydrophilic and hydrophobic properties. An anti-fog coating and a transparent monolithic swellable hydrogel were produced from the PEO1900 hybrid. Swellability and drug release profiles could be easily tuned by varying the ureasil-PEO/ureasil-PPO ratio in the hybrid matrix. Differential scanning calorimetry (DSC) and small angle X-ray scattering (SAXS) analyses indicated that the nanostructure of the hybrid blends could be described by the existence of a biphasic mixture of PEO1900-rich and PPO400-rich phases, with a fraction of the lamellar domains being derived from the PEO1900 crystallinity. A correlation between the nanoscopic features and the kinetics of the swelling mechanism is proposed, based on the results of in situ SAXS analyses. In vitro monitoring using UV-Vis spectroscopy indicated that the kinetics of drug release from the PEO1900:PPO400 hybrid blends could be controlled by varying the proportions of the hydrophilic (PEO1900) and hydrophobic (PPO400) hybrids. The response to pH change and to application of a magnetic field to the PEO1900-magnetite nanocomposite indicated that the production of stimuli-responsive delivery devices based on ureasil-PE should be feasible in the near future.
Keywords: Ureasil-polyether hybrids; PEO: PPO blend; Drug delivery; Swelling; Anti-fog coating